2018
DOI: 10.1177/0022487118791992
|View full text |Cite
|
Sign up to set email alerts
|

Cooperating Teacher as Model and Coach: What Leads to Student Teachers’ Perceptions of Preparedness?

Abstract: Drawing on survey and administrative data on cooperating teachers (CTs) and their preservice student teachers (PSTs) in Chicago Public Schools during 2014-15, this study offers an in-depth look at reports of how CTs engage in their mentoring roles during student teaching, and their influence on PSTs. Our sample includes CTs working with PSTs from across 44 teacher preparation institutions. Central to our analysis is an exploration of CTs as both models of effective instruction and as facilitative coaches on PS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 19 publications
7
58
0
4
Order By: Relevance
“…The lack of heterogeneity of the estimated effects by the effectiveness of the mentor teacher is also an important finding. There is currently wide variation in the effectiveness of teachers assigned as a mentor teachers (Goldhaber et al, 2018); a related literature suggests that mentees are better off in the long-run (in terms of their future productivity) when they have a more effective mentor (Goldhaber et al, 2018;Matsko et al, 2018;Ronfeldt et al, 2018), and our findings suggest that there are few short-run costs to the students in the classrooms hosting student teachers. A possible implication of this for policy and practice is that school districts and teacher education programs should have less concern about placing student teachers in classrooms out of fear that these interns harm students.…”
Section: Discussionmentioning
confidence: 53%
“…The lack of heterogeneity of the estimated effects by the effectiveness of the mentor teacher is also an important finding. There is currently wide variation in the effectiveness of teachers assigned as a mentor teachers (Goldhaber et al, 2018); a related literature suggests that mentees are better off in the long-run (in terms of their future productivity) when they have a more effective mentor (Goldhaber et al, 2018;Matsko et al, 2018;Ronfeldt et al, 2018), and our findings suggest that there are few short-run costs to the students in the classrooms hosting student teachers. A possible implication of this for policy and practice is that school districts and teacher education programs should have less concern about placing student teachers in classrooms out of fear that these interns harm students.…”
Section: Discussionmentioning
confidence: 53%
“…In Tennessee, Ronfeldt, Brockman, and Campbell (2018) linked evaluation data of recent program completers to the evaluation data of their CTs and found that newly hired program completers had better observation ratings based upon the state rubric when their CTs also had better observation ratings; likewise, graduates had better student achievement gains (using Tennessee Value-Added Assessment System [TVAAS] scores) when their CTs did too. In subsequent studies, Ronfeldt, Matsko, et al (2020) found similar patterns between PST and CT observation ratings in Chicago, whereas Goldhaber et al (2018b) identified comparable associations between PST and CT achievement gains in Washington State. These studies suggest the value of policies like the one in place in Tennessee, which establishes minimum teaching evaluation requirements for teachers to serve as CTs.…”
Section: Background/literature Reviewmentioning
confidence: 90%
“…We know of three other studies that attempt to link the coaching practices of CTs with PST outcomes. Matsko et al (2020) looked at all CTs who served in the Chicago area and found that PSTs reported feeling better prepared to teach at the end of their programs when also reporting that their CTs provided more frequent and/or a higher quality of feedback, instructional support, autonomy and encouragement, collaborative coaching, and job assistance. In a subsequent, related study, Ronfeldt, Matsko, et al (2020) also found that PSTs had better first-year observation ratings (based upon district evaluations) when their CTs reported more coaching focused on specific instructional practices, including those evaluated on the same rubric.…”
Section: Background/literature Reviewmentioning
confidence: 99%
“…In student teacher education, or better stated, in educating pre-service teachers-on which this article focuses-mentoring is definitely a very important success factor. It is an essential component in improving pre-service teachers' competence to deal with academic and social issues that they may need to face during their initial college education, as well as to improve their competence in teaching (Matsko et al, 2020;Orland-Barak & Wang, 2020;Richards, 2008;Wexler, 2019). Mentoring can also have a very influential impact to vocational discernment (Campbell et al, 2012;Wexler, 2019), which is very much related to the effectiveness of the curriculum of a pre-service teacher educational institution.…”
Section: Mentoring: Definitions Characteristics and Valuementioning
confidence: 99%